Militant Islam - Jansen, G. H. (Godfrey H.) (Harper colophon books, 1979)
"G.H. Jansen's analysis examines the militancy of Islam from 1800 to the present, emphasizing the resurgence of that militancy in the last decade. He shows us the traditionalists such as the Ayatollah Khomeini of Iran and General Zia of Pakistan who want to take Islam back to strict adherence to the precepts of the Koran, the men of religion anxious to maintain the status quo, and the reformers trying to adapt the faith to the demands of the modern world"--Back cover.